Analisis Scanning Electron Microscopy pada Nacre Sinanodonta (Anodonta) woodiana (Lea, 1834) - Ockstan Jurike Kalesaran; Cyska Lumenta (Journal of Aquaculture and Fish Health, 2021)
Chinese pond shell, Sinanodonta (Anodonta) woodiana (Lea, 1834), is a freshwater bivalve that has essential ecological and economic functions. The microstructure of the nacre is of great interest and is the main attraction for the development of pearl farming. This study aims to describe the microstructure and composition of biomineral elements of the nacre at several shell sizes of S. woodiana. The shell is cut with a small forcepon the ventral margin with a size of 3-5 mm for Scanning Electron Microscpy (SEM). SEM images display that a shell layer consists of periostracum, prismatic and nacre layers. The surface of the nacre layer is an irregular or labyrinth patterned. The nacre tablets are hexagonal, glued to each other, so the nacre tablets become polygonal. Moreover, the microstructure of the nacre tablets is like a brick wall, and the thickness of tablets from 0.43 μm to 0.59 μm. The composition of the biomineral elements are C, O, Ca, and the mineralization mechanism is under the control of aquatic environmental factors that help the process of microstructure formation in nacre.